2016
DOI: 10.1016/j.beproc.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delay and probability combinations on discounting in humans

Abstract: To determine discount rates, researchers typically adjust the amount of an immediate or certain option relative to a delayed or uncertain option. Because this adjusting amount method can be relatively time consuming, researchers have developed more efficient procedures. One such procedure is a 5-trial adjusting delay procedure, which measures the delay at which an amount of money loses half of its value (e.g., $1000 is valued at $500 with a 10-year delay to its receipt). Experiment 1 (n = 212) used 5-trial adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
68
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 29 publications
9
68
1
Order By: Relevance
“…Third, the recently developed 5-trial adjusting delay task was used, which allowed for rapid (~ 1 minute) generation of delay discounting rates. Prior research has validated this task by revealing a close relationship between this rapid task and traditional adjusting delay tasks (Cox and Dallery, 2016; Koffarnus and Bickel, 2014). To our knowledge, this is the first use of drug commodities, namely alcohol and cannabis, with this rapid delay discounting task.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Third, the recently developed 5-trial adjusting delay task was used, which allowed for rapid (~ 1 minute) generation of delay discounting rates. Prior research has validated this task by revealing a close relationship between this rapid task and traditional adjusting delay tasks (Cox and Dallery, 2016; Koffarnus and Bickel, 2014). To our knowledge, this is the first use of drug commodities, namely alcohol and cannabis, with this rapid delay discounting task.…”
Section: Discussionmentioning
confidence: 93%
“…This task has been previously validated against traditional adjusting amount delay discounting tasks (Cox and Dallery, 2016; Koffarnus and Bickel, 2014). Participants were asked to select between some amount of a delayed commodity and half that amount available immediately.…”
Section: Methodsmentioning
confidence: 99%
“…Both systems could be covered by emotions with different relative emphasis on the seeking of positive emotions and the avoidance of negative emotions. In addition, many details of the choice situation are accounted for in the decision-making process, such as required effort (Kurzban et al, 2013), reward delay and payoff riskiness (Bailey, Simpson, & Balsam, 2016;Cox & Dallery, 2016;Dreher, 2013).…”
Section: Prioritising Stimuli Wants and Decision-makingmentioning
confidence: 99%
“…Based on the conceptualization of the multiple modes of discounting, the third purpose of the present study was to investigate if the effects of delay to a destination and probability of a motor vehicle crash depend on the level of the other dimension or if the effects of delay and probability are independent. Previous research using delayed and probabilistic hypothetical money has shown that the probability affects rates of delay discounting, but the delay does not affect rates of probability discounting (Cox & Dallery, 2016;Vanderveldt et al, 2015;Weatherly, Petros, Jónsdóttir, Derenne, & Miller, 2015). Nevertheless, it is unknown whether similar results would be obtained in choices that involve both a delayed reinforcer and a probabilistic punisher, as in the case of texting while driving.…”
mentioning
confidence: 95%